2015 IEEE MTT-S International Microwave Symposium 2015
DOI: 10.1109/mwsym.2015.7166778
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter-wave base station for mobile broadband communication

Abstract: In this paper a millimeter-wave base station operating at 28GHz for mobile communication is introduced. This base station employs 64-elements antenna phased-array to enable adaptive beamforming required for mobile communication. The phased-array is constructed of sub arrays for optimal trade-off between performance and required coverage and beamforming capability. The phased array antenna is integrated with the transceivers on the same printed circuit board (PCB) using industry standard manufacturing process t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…To overcome these challenges, highly directional antennas should be deployed. Antenna array of multiple elements focuses the radio energy into a narrow beam with high gain, which enhances the effective isotropic radiated power (EIRP) without increasing the transmitter power [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome these challenges, highly directional antennas should be deployed. Antenna array of multiple elements focuses the radio energy into a narrow beam with high gain, which enhances the effective isotropic radiated power (EIRP) without increasing the transmitter power [19].…”
Section: Introductionmentioning
confidence: 99%
“…While microstrip antennas have been the subject of many intensive works for decades [20][21][22][23][24], they have been considered in some research efforts reported in the past few years on antenna design aspect of the newly emerging mmW wireless communications [19,[25][26][27][28][29][30][31][32]. Antennas in [19] and [25][26][27][28] are mainly designed to operate in one of the target frequency bands, as listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the real present driver of the mm-wave technology are communications. Their role in our days society has put a lot of money on the table, triggering an explosion of work to satisfy new created service necessities [600]- [603], [608]- [609], [632]- [636]. The literature in the topic is tremendously vast, and the commercial race, phrenetic.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Third, there will be a cost reduction caused by the well-known effect of economies of scale. This will not only be provided by the massive development of all kind of radar types (SRR, MRR and LRR) as points [659], but the development to come from the telecommunications industry has much to say [600]- [603], [608]- [609], [632]- [636]. Regarding to this unavoidable relationship between both areas, a further reason can be added in this point.…”
Section: The Mm-wave Bandmentioning
confidence: 99%